STRATEGI MENINGKATKAN MINAT BACA MASYARAKAT MELALUI PROGRAM LAYANAN PERPUSTAKAAN KELILING “ LAN ELING” PADA DINAS ARSIP DAN PERPUSTAKAAN DAERAH KABUPATEN BULELENG: Meningkatkan Minat Baca - Asoka Kamadhuk (Universitas Pendidikan Ganesha, 2026)
Reading interest is a key indicator in building a strong and sustainable literacy culture. However, limited access to reading materials in rural areas remains a major challenge. This study aims to explore the strategies implemented in the LAN ELING (Mobile Library Service) program by the Department of Archives and Regional Library of Buleleng Regency to enhance public reading interest. A qualitative descriptive approach was used, with data collected through in-depth interviews, direct observation, and documentation.The results of the study show that the strategies applied in the LAN ELING program include a proactive outreach approach, interactive literacy activities (such as storytelling, quizzes, and group reading), collaboration with schools and village officials, and active promotion through various media. The program has proven effective in increasing reading interest, especially among children and students in rural areas. Positive impacts include the emergence of community reading corners and greater school engagement in literacy efforts. Nevertheless, the program faces several challenges, such as limited vehicle availability, outdated book collections, and low reading interest among adults.This study concludes that the LAN ELING mobile library service is an effective strategy for promoting literacy and can be replicated in other regions with cross-sector collaboration and continuous innovation.